Women Empowerment through IFAD’s Rural Development Project - Ibrahim, Hind Bushra Ahmed (Advances in Social Sciences Research Journal, 2017)
Rural women play a crucial role in agricultural development and allied fields. In the present study an attempt has been made to analyse the influence of IFAD rural development project on women empowerment. The results showed that majority of the women had medium or low level of education and they play important role in agricultural production in their area. Most of them participated in agricultural training and were agreed upon the suitability of training methods.